2010
DOI: 10.1177/0956797610383437
|View full text |Cite
|
Sign up to set email alerts
|

Power Posing

Abstract: Humans and other animals express power through open, expansive postures, and they express powerlessness through closed, contractive postures. But can these postures actually cause power? The results of this study confirmed our prediction that posing in high-power nonverbal displays (as opposed to low-power nonverbal displays) would cause neuroendocrine and behavioral changes for both male and female participants: High-power posers experienced elevations in testosterone, decreases in cortisol, and increased fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
300
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(346 citation statements)
references
References 29 publications
7
300
7
1
Order By: Relevance
“…In 2010 Carney et al asserted that "a person can, by assuming two simple 1-min poses, embody power and instantly become more powerful [which] has real-world, actionable implications" [14] thereby coining the concept of power poses. Yap et al later identified a set of behaviors such as increased risk-taking or cheating which they showed could be induced through incidental power poses, that is, expansive postures imposed by the design of the environment [65].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010 Carney et al asserted that "a person can, by assuming two simple 1-min poses, embody power and instantly become more powerful [which] has real-world, actionable implications" [14] thereby coining the concept of power poses. Yap et al later identified a set of behaviors such as increased risk-taking or cheating which they showed could be induced through incidental power poses, that is, expansive postures imposed by the design of the environment [65].…”
Section: Introductionmentioning
confidence: 99%
“…For both tasks, this had to be done while keeping one's index fingers on the respective end points of the manipulated line. Thus, the increase condition did not actually imply taking an expanded initial posture and changing it into a constricted one (or vice versa for the decrease condition), as would be the case for a power posing induction (here, participants usually adopt an expanded vs. constricted posture with their whole body while sitting or standing; Carney, Cuddy, & Yap, 2010;Cuddy, Wilmuth, Yap, & Carney, 2015;Garrison, Tang, & Schmeichel, 2016;Ranehill et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…arms spread wide, chest puffed out) report not only feeling more powerful, but also being more likely to take risks. These participants also show increases in testosterone (Carney, Cuddy, & Yap, 2010). So while the entrance into the emotional state may be different (purposefully feeling an emotion versus physicalizing first), the end result may be the same.…”
mentioning
confidence: 99%